(untitled) (JOURNAL OF ADVANCES IN AGRICULTURE, 2016)
Utilization of urea super granule (USG) with raised bed cultivation system for transplanted boro (winter, irrigated) rice production is a major concern now days. A field experiment was conducted in the chuadanga district of Bangladesh to compare the two cultivation methods: deep placement of USG on raised bed with boro rice, and prilled urea (PU) broadcasting in conventional planting. Results showed that USG in raised bed planting increased grain yields of transplanted boro rice by up to 18.18% over PU in conventional planting. Deep placement of USG in raised bed planting increased the number of panicle m-2, number of grains panicle-1 and 1000-grains weight of boro rice than the PU in conventional planting. Better plant growth was observed by deep placement of USG in raised bed planting compared to PU in conventional planting. Sterility percentage and weed infestation were lower on USG in raised bed planting compared to the PU in conventional planting methods. Forty seven percent irrigation water and application time could be saved by USG in raised bed planting than PU in conventional planting. Deep placement of USG in bed saved N fertilizer consumption over conventional planting. Water use efficiency for grain and biomass production was higher with deep placement of USG in bed planting than the PU broadcasting in conventional planting methods. Similarly, agronomic efficiency of N fertilizer by USG in bed planting was significantly higher than the PU broadcasting in conventional planting. This study concluded that deep placement of USG in raised bed planting for transplanted boro rice is a new approach to achieve fertilizer and water use efficiency as well as higher yield and less water input compared to existing agronomic practices in Bangladesh.